Complex dyskinesias in Parkinson patients on levodopa/carbidopa intestinal gel. (December 2019) - Marano, Massimo; Naranian, Taline; di Biase, Lazzaro; Di Santo, Alessandro; Poon, Yu-Yan; Arca, Roberta; Cossu, Giovanni; Marano, Pietro; Di Lazzaro, Vincenzo; Fasano, Alfonso
Abstract: Background: Levodopa-carbidopa intestinal infusion is an effective treatment for motor fluctuations in Parkinson's disease. However, it has been recently associated with emergent complex/atypical dyskinesias. We sought to characterize patients who developed these dyskinesias after levodopa infusion initiation, and to compare these patients to a control population with conventional motor fluctuations. Methods: 208 Parkinson's disease patients, treated with levodopa intestinal infusion due to motor fluctuations, were screened for onset and/or worsening of dyskinesias after initiation of levodopa infusion, resistant to the routine titration, and presenting with atypical or unexpected patterns. Patients with extensive follow-up data were enrolled for a longitudinal analysis. Cases were compared to a control sample with conventional motor fluctuations in order to investigate predisposing factors, difference in dyskinesia phenotype, management strategies and dropouts. Results: Thirty patients out of 208 (14.4%) reported atypical (i.e. long-lasting) biphasic, biphasic-like (i.e. continuous) or mixed (peak-dose and continuous biphasic) dyskinesias after levodopa infusion. They were compared at baseline and follow-up to a sample of 49 patients with conventional motor fluctuations on levodopa infusion. Both groups had similar demographic and clinical features, except the former having higher prevalence of biphasic dyskinesias while on oral therapy. Biphasic-like dyskinesias in nearly half the number of cases improved with increasing the dopaminergic load, while mixed dyskinesias had the worst outcome and highest dropout rate (58%). Conclusions: Atypical biphasic, biphasic-like and complex dyskinesias could hinder the course of patients treated with levodopa infusion. This study further informs the selection process of advanced therapies, particularly in dyskinetic patients. Highlights: Roughly 14% patients on LCIG manifests complex dyskinesias. Complex dyskinesias are commonly biphasic-like. A subgroup with superimposed peak dyskinesias more frequently discontinue LCIG. Pre-existent biphasic dyskinesias might promote complex dyskinesias after LCIG. LCIG should be carefully adopted in patients with troublesome dyskinesias.